The colour fantastic chromatic worlds of silent cinema - Fossati, Giovanna 1971-; Yumibe, Joshua 1974-; Street, Sarah 1958-; Rongen-Kaynakçi, Elif; Lameris, Bregt 1973-; Jackson, Victoria ca. 20./21. Jh (Amsterdam University Press, 2020)
Sparked by a groundbreaking Amsterdam workshop titled "Disorderly Order: Colours in Silent Film," scholarly and archival interest in colour as a crucial aspect of film form, technology and aesthetics has enjoyed a resurgence in the past twenty years. In the spirit of the workshop, this anthology brings together international experts to explore a diverse range of themes that they hope will inspire the next twenty years of research on colour in silent film. Taking an interdisciplinary approach, the book explores archival restoration, colour film technology, colour theory, and experimental film alongside beautifully saturated images of silent cinema
Title from publisher's bibliographic system (viewed on 28 Dec 2020)
Nonfiction and amateur cinema -- 1. Fireworks and Carnivals: Applied and Natural Colours in Italian Home Movies / Elena Gipponi -- 2. Liminal Perceptions: Intermediality and the Exhibition of Nonfiction Film / Liz Watkins -- 3. Rough Seas: The Blue Waters of Early Nonfiction Film / Jennifer Peterson -- Naturel-colour processes: theory and practice -- 4. 'Taking the color out of color': Two-Colour Technicolor, The Black Pirate, and Blackened Dyes / John Belton -- 5. Why Additive? Problems of Colour and Epistemological Networks in Early (Film) Technology / Benoit Turquety -- 6. Ziegfeldized Slapstick, Useful Comedy: Mack Sennett's Slapstick Comedies under the Influence of Natural Colour / Hilde D'Haeyere -- 7. Kinemacolor and Kodak: The Enterprise of Colour / Frank Gray -- Intermediality and advertising -- 8. Rainbow Ravine: Colour and Animated Advertising in Times Square / Kirsten Moana Thompson -- 9. Kodachrome's Hope: The Making and Promotion of McCall Colour Fashion News / Natalie Snoyman -- 10. Chromatic Objects: Colour Advertising and French Avant-garde Films of the 1920s / Federico Pierotti -- Archiving and restoration: early debates and current practices -- 11. La Ligue du Noir et Blanc: French Debates on Natural Colour Film and Art Cinema 1926 -- 1927 / Bregt Lameris -- 12. A Material-Based Approach to the Digitization of Early Film Colours / David Pfluger
Keywords: Geschichte Anfänge-1930; Color motion pictures / History and criticism; Silent films / History and criticism; Farbe; Stummfilm; Konferenzschrift -- 2015 -- Amsterdam